Psychometric Properties of the Family Functioning Styles Scale in School Adolescents from the City of Arequipa - Pulcha Huayllaro, Dayeli Adriana (2024)
Given the important relationship between family functioning and the developmental stage of adolescence, the main purpose of the present study was to analyze the psychometric properties of the Family Functioning Styles Scale in adolescents from the city of Arequipa. A sample of 505 school students from different local institutions was used. The test was subjected to an Aiken V analysis, as well as to an Exploratory Factor Analysis. For the Confirmatory Factorial Analysis, three models were submitted, finding in the second one the following values: X2/gl= 1.77; CFI= 0.967; TLI= 0.962; SRMR= 0.052; and RMSEA[IC90%]= 0.052, confirming the three-factor factorial structure, which corresponds to the original theory. Likewise, reliability was estimated using Cronbach’s Alpha test and McDonald’s Omega test, resulting in both cases with adequate internal consistency indices.